Pengembangan Aplikasi Mobile POVSHOT untuk Penjualan Foto Online Menggunakan Flutter dan MySQL - Cahaya Citra Azzahro; Johan Krisbima Abi; Octavian Dava Putra; Agil Gilang Chandra Saputra; Fadlil Liwaul Hamdi; Ach. Fasihul Lisan (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
The rapid advancement of information and communication technology has transformed and opened business perspectives and operations, particularly in UMKM the photography industry. As the demand for online photography services continues to rise, it is crucial for service providers to develop efficient information systems to manage photo sales effectively. The research titled